1999
DOI: 10.1038/sj.ejhg.5200381
|View full text |Cite
|
Sign up to set email alerts
|

Associations of IGF2 ApaI RFLP and INS VNTR class I allele size with obesity

Abstract: Body mass index (BMI) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 29 publications
3
24
2
Order By: Relevance
“…Conversely, it has also been shown that class III homozygote children and young adults may have a greater BMI than class I carriers (4,6). By contrast, we found no association between INS VNTR class as inferred by the Ϫ23Hph1 genotype and BMI in 7,999 middle-aged men and women, confirming previous reports based on middle-aged study participants (7,22).…”
Section: Discussionsupporting
confidence: 36%
“…Conversely, it has also been shown that class III homozygote children and young adults may have a greater BMI than class I carriers (4,6). By contrast, we found no association between INS VNTR class as inferred by the Ϫ23Hph1 genotype and BMI in 7,999 middle-aged men and women, confirming previous reports based on middle-aged study participants (7,22).…”
Section: Discussionsupporting
confidence: 36%
“…In lung, the most variant genes include integrin-␤2, which has been shown to predispose individuals to recurrent bacterial infections (16,20), and antileukoproteinase, which is involved in several chronic and acute diseases of the respiratory tract (4,35). In liver, the most variant genes include insulin-like growth factor 2, a putative susceptibility factor for obesity (9,12,32); fibrinogen-␥, defects of which are a cause of thrombophilia (26,27); and hepatic lipase, a complete deficiency of which causes coronary atherosclerosis and premature dyslipidemia (17,33). Each of the other 13 tissue types contains samples from less than 3 different individuals.…”
Section: Housekeeping or Maintenance Genes And Their Tissuespecific Ementioning
confidence: 99%
“…16,17 As impaired fetal growth is a risk factor for adult metabolic diseases, 18 genes like IGF2 are attractive candidates to explain susceptibility to disorders such as T2D and obesity, and accordingly several association studies have been conducted. [19][20][21][22][23][24][25][26][27][28][29] In a sample of British middle-aged men, the minor allele of the 820G4A (ApaI) single nucleotide polymorphism (SNP) located in the 3 0 untranslated region of the IGF2 gene was associated with lower body mass, lower body mass index (BMI) and higher IGF2 levels. 20,21 Although the association with lower BMI was replicated in an Israeli sample, 22 several studies failed to confirm this.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28][29] In a sample of British middle-aged men, the minor allele of the 820G4A (ApaI) single nucleotide polymorphism (SNP) located in the 3 0 untranslated region of the IGF2 gene was associated with lower body mass, lower body mass index (BMI) and higher IGF2 levels. 20,21 Although the association with lower BMI was replicated in an Israeli sample, 22 several studies failed to confirm this. [23][24][25] Moreover, a study in American participants even showed that minor allele carriers had a greater fat body mass.…”
Section: Introductionmentioning
confidence: 99%